Optimization of direct anti‐viral agent treatment schedule: Focus on HCV genotype 3. Issue 2 (1st March 2018) - Morisco, Filomena; Granata, Rocco; Camera, Silvia; Ippolito, Antonio; Milella, Michele; Conti, Fabio; Masetti, Chiara; Smedile, Antonella; Tundo, Paolo; Santantonio, Teresa; Valvano, Maria Rosa; Termite, Antonio; et al.
Abstract : Background and aim: Direct antiviral agents (DAAs) have led to high sustained virological responses (SVR) in hepatitis C virus (HCV) patients. However, genotype 3 patients respond to treatment in a suboptimal way. This study aims to identify which of the several treatment schedules recommended for genotype 3 would constitute the best option. Methods: Twenty‐four Italian centers were involved in this real‐life study of HCV genotype 3 patients treated with DAAs. To expand the number of cases, we conducted a systematic review of the literature on the outcome of genotype 3 patients treated with DAAs. Results: A total of 233 patients with HCV genotype 3 were enrolled. Cirrhotic patients accounted for 83.7%. Overall, the SVR12 rate was achieved by 205 patients (88.0%); the SVR rates were 78.8% after sofosbuvir/ribavirin, 92.5% after sofosbuvir/daclatasvir ± ribavirin, and 100% after sofosbuvir/ledipasvir (seven patients). No difference in rate of SVR was observed in cirrhotic and non‐cirrhotic patients (92.2 vs 94.4) using a combination regimen of NS5A and NS5B inhibitors. The systematic review of the literature provided data of 3311 patients: The mean weighted SVR12 rate was 84.4% (CI: 80.4–87.8); the rates varied from 79.0% (CI: 70.9–85.3) with sofosbuvir/ribavirin, to 83.7% (CI: 66.2–93.1) with sofosbuvir/ledispavir, and to 88.2% (CI: 83.3–91.7) with sofosbuvir/daclatasvir. Conclusions: Our results reinforce the concept that patients with HCV genotype 3 should no longer be considered difficult‐to‐treat individuals. The optimal therapeutic regimen for these patients appears to be the combination sofosbuvir/daclatasvir, administered for 12 weeks without the use of RBV in non‐cirrhotic patients. In cirrhotics the meta‐analytic approach suggests extending therapy to 24 weeks.